The Impact of Artificial Intelligence In English Class: Real Assistance or Real Learner? - Zebua, Elwin P. (Indonesian Research Journal on Education, 2025)
Artificial intelligence or AI has quietly revolutionized how students approach English language learning, yet academics still fighting with fundamental question about its true educational value. This study examined 48 second-semester PGSD students of FKIP at Universitas Nias through careful classroom observation during 2024/2025 academic year. In conducting this research, the researcher chose to observe and document real students’ behaviors as they naturally unfolded in fifteen weeks of English subject class. As predicted, the emerged situation was AI tools undeniably help students completing any English tasks more efficiently and tackle challenging materials with greater confidence. However, the researcher viewed worrying patterns of over-dependence that seemed to reduce the value of critical thinking and authentic language production. The research subjects drown into feared pattern: reaching for AI assistance before attempting independent problem-solving, even for the easiest tasks. The research findings suggest that AI functions best as a supportive tool (not as all-time assistant) when students remain mindful of its limitations, but current implementation lacks the pedagogical structure necessary for optimal learning outcomes.